Fluorescent glutathione probe based on MnO2-phenol formaldehyde resin nanocomposite - Wang, Xudong; Wang, Dan; Guo, Yali; Yang, Chengduan; Liu, Xiaoyu; Iqbal, Anam; Liu, Weisheng; Qin, Wenwu; Yan, Dan; Guo, Huichen (Biosensors & bioelectronics, 2016)
MnO2-phenol formaldehyde resin (MnO2-PFR) nanocomposite is successfully prepared by a simple chemical reduction process. The resultant MnO2-PFR nanocomposite is well characterized. The absorption band of non-fluorescent MnO2 nanosheets overlaps well with the fluorescence emission of PFR nanoparticles. The green fluorescence of PFR in this nanocomposite can be effectively quenched by fluorescence resonance energy transfer from PFR to MnO2. In the presence of glutathione (GSH), the fluorescence of PFR could be recovered due to MnO2 was reduced to Mn2+ by GSH. The nanocomposite can be use for detecting glutathione in blood serum. •MnO2-phenol formaldehyde resin (MnO2-PFR) nanocomposite is successfully prepared by a simple chemical reduction process.•In the presence of glutathione (GSH), the fluorescence of PFR could be recovered due to MnO2 was reduced to Mn2+ by GSH.•MnO2-PFR nanocomposite shows remarkable properties including very fast and simple, onestep, cost-effective as well as environmental-friendly.•The nanocomposite can be use for detecting glutathione in blood serum.